An overview on antidiabetic medicinal plants having insulin mimetic property - Patel D.K.; Prasad S.K.; Kumar R.; Hemalatha S. (My University, 2025)
Diabetes mellitus is one of the common metabolic disorders acquiring around 2.8% of the world's population and is anticipated to cross 5.4% by the year 2025. Since long back herbal medicineshave been the highly esteemed source of medicine therefore, they have become a growing part ofmodern, high-tech medicine. In view of the above aspects the present review provides profiles of plants (65 species) with hypoglycaemic properties, available through literature source from variousdatabase with proper categorization according to the parts used, mode of reduction in bloodglucose (insulinomimetic or insulin secretagogues activity) and active phytoconstituents having insulin mimetics activity. From the review it was suggested that, plant showing hypoglycemicpotential mainly belongs to the family Leguminoseae, Lamiaceae, Liliaceae, Cucurbitaceae, Asteraceae, Moraceae, Rosaceae and Araliaceae. The most active plants are Allium sativum, Gymnema sylvestre, Citrullus colocynthis, Trigonella foenum greacum, Momordica charantiaand Ficus bengalensis. The review describes some new bioactive drugs and isolated compoundsfrom plants such as roseoside, epigallocatechin gallate, beta-pyrazol-1-ylalanine, cinchonain Ib, leucocyandin 3-O-beta-d-galactosyl cellobioside, leucopelargonidin-3-O-alpha-L rhamnoside, glycyrrhetinic acid, dehydrotrametenolic acid, strictinin, isostrictinin, pedunculagin, epicatechin and christinin-A showing significant insulinomimetic and antidiabetic activitywith more efficacy than conventional hypoglycaemic agents. Thus, from the review majorly, theantidiabetic activity of medicinal plants is attributed to the presence of polyphenols, flavonoids,terpenoids, coumarins and other constituents which show reduction in blood glucose levels. The review also discusses the management aspect of diabetes mellitus using these plants and theiractive principles.